2020
DOI: 10.1029/2019jb018299
|View full text |Cite
|
Sign up to set email alerts
|

Directivity Modes of Earthquake Populations with Unsupervised Learning

Abstract: We present a novel approach for resolving modes of rupture directivity in large populations of earthquakes. A seismic spectral decomposition technique is used to first produce relative measurements of radiated energy for earthquakes in a spatially compact cluster. The azimuthal distribution of energy for each earthquake is then assumed to result from one of several distinct modes of rupture propagation. Rather than fitting a kinematic rupture model to determine the most likely mode of rupture propagation, we i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 54 publications
1
10
0
Order By: Relevance
“…[73,168,190]), but for statistical analysis and ground motion prediction larger scale inversion of greater numbers of events is essential. Combining and developing the large scale inversion methods of Shearer et al [119] and Ross et al [191] with improved statistical analysis of the uncertainties and biases caused by simplifying assumptions and methods (e.g. [130,192,193]) is proving fruitful.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[73,168,190]), but for statistical analysis and ground motion prediction larger scale inversion of greater numbers of events is essential. Combining and developing the large scale inversion methods of Shearer et al [119] and Ross et al [191] with improved statistical analysis of the uncertainties and biases caused by simplifying assumptions and methods (e.g. [130,192,193]) is proving fruitful.…”
Section: Discussionmentioning
confidence: 99%
“…[119] and Ross et al . [191] with improved statistical analysis of the uncertainties and biases caused by simplifying assumptions and methods (e.g. [130,192,193]) is proving fruitful.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the directivity pattern caused by the updip propagation is become evident only around the surface exposure or around its updip projection (Somerville 2003). These updip effects, without stations right on top of the rupture (as AMT station) are very difficult to be observed (Ross et al 2020). However, in Fig.…”
Section: Spatial Distribution Of Ground Motion From Hybrid Broad-band...mentioning
confidence: 95%
“…Earthquake ruptures can be classified in pure unilateral or pure bilateral (symmetric) ruptures, as well as asymmetric bilateral ruptures, describing an intermediate case between the two previous models. It is well know that a predominance of unilateral ruptures is observed for large earthquakes (McGuire et al, 2002); however, recent studies demonstrated that directivity might be also a common feature of small to moderate events (e.g., Kane et al, 2013;Kurzon et al, 2014;Calderoni et al, 2015;Meng et al, 2020;Ross et al, 2020). So far, rupture directivity has also been identified for a few cases of weak fluid-injection induced earthquakes (Folesky et al, 2016;López-Comino and Cesca, 2018;Király Proag et al, 2019;Wu et al, 2019) and fluid-induced microcracks or acoustic emission (AE) events in mine-scale hydraulic fracturing (HF) experiments (Dahm, 2001), suggesting that such properties could persist at smaller magnitudes.…”
Section: Introductionmentioning
confidence: 99%